Pigmented contact dermatitis to p-paraphenylenediamine in a textile factory worker - Mrinal Gupta (Our Dermatology Online, 2017)
Pigmented contact dermatitis (PCD) is a noneczematous variant of contact dermatitis, characterized clinically by hyperpigmentation with little or no signs of dermatitis. The commonly implicated agents causing PCD include cosmetics like fragrances, lipsticks and kumkum, preservatives, optical whiteners, benzyl salicylate and metallic compounds like nickel sulphate and nickel oxide. We present a case of PCD in a 45-year old textile factory worker, who presented with gradually progressive asymptomatic hyperpigmentation of the face which started after he started working in a textile factory. Patch test revealed sensitization to p-Paraphenylenediamine, thereby confirming the diagnosis of PCD to p-Paraphenylenediamine.